A MODEL OF INDUSTRIAL WASTE WATER POLLUTION CONTROL POLICY IN PURWAKARTA REGENCY USING SYSTEMS THINKING APPROACH: Using a systems thinking approach in a model of industrial waste water control policy - Hapsari, Indi Annisa (Jurnal Administrasi Negara, 2022)
The progress of development, especially in the industrial sector is also followed by the consequences of pollution. Wastewater contributes an extensive impact and a major problem to the environment. This research aims to analyze the implementation of Industrial Wastewater Pollution Control Policy in Purwakarta District. It also tries to design an implementation model of the industrial wastewater control policy and develop an action plan for solving emerging problems. This research employs a descriptive, qualitative method. It uses systems thinking analysis based on the 6 (six) Weaver’s variables as an effort to understand the structure of an observed system, and to identify the behavior patterns to get a conclusion over the events occurring in the system. The research results showed that the implementation of industrial wastewater control policy in Purwakarta District was not effective. In terms of reward and punishment mechanism, some PROPER and administrative sanctions had been imposed for those violating the rules, however they were not effective yet. In terms of supervision, some Standard Operating Procedure (SOP) and supervision plan had yet to be issued to support the policy implementation. Likewise, the quality and quantity of resources were inadequate. In addition, the industries were less informed with the nuts and bolts of the policy. Despite existing support of disposition and attitudes, it was considered insufficient. Thus, in order to create harmonization of regulations and controls performed by Purwakarta District Environment Office, it is necessary to integrate policies to control industrial wastewater pollution by formulating a new local regulation (updating) for integrated management of water resources including the division of roles among local agencies.